Kebiasaan Melanggar Peraturan Pengguna Jalan Sebagai Objek Penciptaan Karya Seni Lukis - Pratama, Randi; Khairunnisa, Khairunnisa; Fajrina, Rahma Melisha; Gani, Maulid Hariri (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
Abstract The habit of violating the rules by road users became a source of ideas in creating this work of art. The asphalt road and the icons on the road are used as objects for creating works. Starting from observing the behavior and habits of road users and public facilities who do not comply with applicable regulations, violate traffic signs, disobey road markings and so on. The author uses forms or icons that are often found on the streets, such as; traffic signs, marking lines, road asphalt, car tire tracks and so on onto the canvas using a realist-symbolic style. The realist-symbolic concept is used to convey messages to people who see or enjoy this work. The method used in the process of making this work goes through several stages, namely; (1) observation stage (2) contemplation stage (3) sketch stage (4) embodiment stage. Keywords: the habit of breaking the rules, streets, painting